A Molecular Hero Suit for In Vitro and In Vivo DNA Nanostructures. Issue 26 (15th April 2019) - Kizer, Megan E.; Linhardt, Robert J.; Chandrasekaran, Arun Richard; Wang, Xing
Abstract: Precise control of DNA base pairing has rapidly developed into a field full of diverse nanoscale structures and devices that are capable of automation, performing molecular analyses, mimicking enzymatic cascades, biosensing, and delivering drugs. This DNA‐based platform has shown the potential of offering novel therapeutics and biomolecular analysis but will ultimately require clever modification to enrich or achieve the needed "properties" and make it whole. These modifications total what are categorized as the molecular hero suit of DNA nanotechnology. Like a hero, DNA nanostructures have the ability to put on a suit equipped with honing mechanisms, molecular flares, encapsulated cargoes, a protective body armor, and an evasive stealth mode. Abstract : DNA nanostructures perform a wide array of functions from drug delivery to molecular circuits. Their applications in in vitro and in vivo circumstances require special thought in developing a molecular hero suit. This suit equips specialized DNA nanostructures with cell targeting agents, encapsulating therapeutic cargo, and a body armor to protect them from degradation.